Expectations and Speculation in the Natural Gas Markets - Christina Anderl; Guglielmo Maria Caporale (CESifo GmbH, 2024)
This paper aims to assess the role of expectations as a determinant of the real price of natural gas. To measure expectations-driven speculative demand three approaches are followed, which are based respectively on using natural gas inventories consistently with the theory of storage (Kilian and Murphy, 2014), the futures spread (Valenti, 2022), and functional shocks defined as shifts in the entire risk-adjusted natural gas futures term structure (Inoue and Rossi, 2021). Three specifications of a structural VAR (SVAR) model are then estimated based on each of those approaches in turn. The results suggest that expectations, especially when measured as functional shocks, lead to strong and persistent increases in the real price of natural gas. A shock decomposition exercise shows that the price of natural gas responds primarily to changes in the curvature of its futures term structure, which indicates that medium-term expectations are the main driver of permanent increases in the spot price of natural gas. Further, the functional natural gas price shocks seem to account for around half of the variation in the real price of natural gas.
Keywords: D84; G15; Q41; Q43; 330; natural gas price; expectations; speculation; inventories; functional shocks; structural VAR (SVAR)